2009
DOI: 10.2320/matertrans.m2009267
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Microstructure on Corrosion of Molybdenum-Bearing Titanium Alloys in High Chloride and Acidic Solution at High Temperature

Abstract: The effect of microstructure on corrosion of heat-treated Ti-15Mo alloys was investigated by Electrochemical impedance spectroscopy (EIS), Field emission scanning electron microscopy (FE-SEM), Transmission electron microscopy (TEM) and Energy dispersive X-ray analysis (EDAX). The sample subjected to solution heat treatment (ST) had a single phase and samples subjected to aging heat treatment at 600 C had phase precipitation in phase. EIS results showed that the corrosion resistance of the aging heat-treated sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…It has been documented that alloying Ti with sufficient quantities of molybdenum (Mo) provides high corrosion resistance (Ref 9,10). In our work, Ti-15 mass% Mo alloy was found to be a highly corrosion-resistant alloy instead of rare metal in high level acidic solution at elevated temperatures (Ref 11,12).…”
Section: Introductionmentioning
confidence: 55%
“…It has been documented that alloying Ti with sufficient quantities of molybdenum (Mo) provides high corrosion resistance (Ref 9,10). In our work, Ti-15 mass% Mo alloy was found to be a highly corrosion-resistant alloy instead of rare metal in high level acidic solution at elevated temperatures (Ref 11,12).…”
Section: Introductionmentioning
confidence: 55%
“…In the case of the Ti-Mo binary alloy, microgalvanic coupling occurred between the Mo-poor phase and Mo-rich phase, and the active part of the phase was highly susceptible to corrosion. 13) Hence, as for the Ti-8Mo-5Fe alloy in Fig. 7, corrosion preferentially occurred at the phase in Sample HB2-2 in the same way as Ti-Mo alloy.…”
Section: Surface Characterization After Corrosion Of Agingmentioning
confidence: 93%
“…This is explained by the fact that the resistance in the low-frequency region is the passive film resistance, and the film capacitance appears in the EIS spectrum. 13) At 5 days, the EIS spectra showed another resistance component in the mid-frequency region. This resistance in the mid-frequency region was considered to be caused by -phase dissolution.…”
Section: Electrochemical Impedance Spectroscopic (Eis) Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] Meanwhile, it has been reported that titanium alloys with sufficient content of Mo provides the high corrosion resistance. [6][7][8][9] Nishimura 8) found that a Ti-15Mo alloy (mass%), which was developed in the 1950s as a corrosion resistance titanium alloy, 10) exhibits an extremely high corrosion resistance in highly acidic solution at 373 K, which is able to against the crevice corrosion in seawater at the high temperature. However, this alloy shows a low yield strength in the as-solution treated condition because of its deformation by f332gh113i twinning.…”
Section: Introductionmentioning
confidence: 99%